THE IMPACT OF BASIC COMPONENTS OF INTELLECTUAL CAPITAL ON THE PROFITABILITY OF JORDANIAN COMMERCIAL BANKS (2007- 2012) - Baker Aledwan (European Scientific Journal, ESJ, 2014)
This study aimed to examine the impact of intellectual capital disclosure (ICD) on the profitability of Jordanian commercial banks. To achieving these objectives data were collected from annual reports of 13 Jordanian commercial banks for the period (2007-2012). The study applied content analysis techniques to gather data for the disclosure of intellectual capital components (human capital, structural capital and relational capital), while earnings per share (EPS) and the market value of the company (MV) were used as profitability measures. The study revealed that there was statistically significant effect of human capital and structural capital on profitability of banks and their market value, while showing no such effect of the relational capital.